PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. PUTRA KELANA MAKMUR BATAM - Eki Saputra; Lukmanul Hakim; Dini Anggraini (University of Riau Kepulauan, 2017)
The purpose of the research is to determine: the influence of organizational culture, work environment, leadership on the performance of employees at PT. Putra Kelana Makmur Batam. The subjects of this research are employees of PT. Putra Kelana Makmur Batam taken of 52 employees. Data were collected through questionnaires. The analysis used was validity, reliability testing, classical assumption test, multiple linear regression analysis, testing hypothesis. The results of this research indicate that (1) an organizational culture influence on employees’ performance. It can be seen organizational culture variable (X1) that t value (14.541) and significance (0.000) from 0005 and shows a significant difference between organizational culture on employees’ performance. (2) The working environment influence on employees’ performance. It can be seen that working environment variables (X2) t value between work environment affect the performance of employees is 2,599. The significance value 0.014 0.05 which means that the relationship is significant. Based on the data obtained, the decision was to declare a significant difference between the work environment influences on employee performance.3) Leadership (X3) influence on employees’ performance. Significance value 0.00 0.05 which means that the relationship is significant. Based on the data obtained, the result was to declare a significant difference between the leadership on employees’ performance.Analysis of determination coefficient indicates that the variable X (organizational culture, work environment, leadership) have positive effect on the variable Y (employee performance) and have a degree of influence by 99.7%. Significant testing on the work culture affects the performance of employees at PT. Putra Kelana Makmur Batam shows that t is greater than t table which amounted organizational cultureis 14.541, work environment is 2599 and leadership is 3.921 its mean that the hypothesis can be accepted.